2008
DOI: 10.21236/ada484801
|View full text |Cite
|
Sign up to set email alerts
|

The Low-Temperature Vibrational Behavior of Pentaerythritol Tetranitrate

Abstract: Approved for public release; distribution is unlimited.ii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…When compressed at room temperature (298 K), PETN shows a change in the molecular symmetry from S 4 → D 2 between 6.3 and 10.9 GPa (figures 2 and 3). The exact pressure of the symmetry transformation is known to be strongly dependent on the conditions within the cell as well as the crystalline phase (i.e., powder or single crystal) (27), but in this work, the transition pressure was near 8.1 GPa. The transformation can be visually observed since single-crystal PETN normally appears translucent, but after the transformation, the sample looks slightly opaque.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…When compressed at room temperature (298 K), PETN shows a change in the molecular symmetry from S 4 → D 2 between 6.3 and 10.9 GPa (figures 2 and 3). The exact pressure of the symmetry transformation is known to be strongly dependent on the conditions within the cell as well as the crystalline phase (i.e., powder or single crystal) (27), but in this work, the transition pressure was near 8.1 GPa. The transformation can be visually observed since single-crystal PETN normally appears translucent, but after the transformation, the sample looks slightly opaque.…”
Section: Resultsmentioning
confidence: 70%
“…Under hydrostatic conditions with nearly no sample strain, the modifications in the vibrational spectra indicated a symmetry change to the D 2 molecular geometry, but no crystallographic phase transition was observed between ambient pressure and 14 GPa. Several less hydrostatic samples with a higher degree of stress/strain showed a significant loss of vibrational resolution in both the number of visible peaks and intensity, presumably due to the activation of the PETN slip planes (27). The loss of intensity, coupled with the disappearance of several vibrational peaks, may have been misconstrued as a phase transition (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed changes in Raman spectra of single-crystal PETN using N 2 , Ne, and He as pressure media, but found that the threshold pressures varied significantly with the pressure medium [9]. They concluded that the appearance of the new phase is correlated with the onset of non-hydrostatic response of the pressure medium.…”
Section: Introductionmentioning
confidence: 99%
“…Ciezak and Jenkins [9] observed peak splittings between 6 and 9 GPa in Raman spectra of PETN powder using Ne as a pressure medium. They also observed changes in Raman spectra of single-crystal PETN using N 2 , Ne, and He as pressure media, but found that the threshold pressures varied significantly with the pressure medium [9].…”
Section: Introductionmentioning
confidence: 99%